Design of Webinar Information System for People with Hearing Impairments - Irfan D. Sumitra; Erik Wirawan; M. Putra; I. Kusumaningrat; Hanhan Maulana (Indonesian Journal of Community and Special Needs Education, 2021)
This research aimed to design a webinar platform that can help the deaf understand information while attending online seminars using sign language interpreter features. That way, the deaf will have no difficulty understanding the material being delivered by the speaker. This research method used descriptive methods to describe the problems faced by deaf webinar participants, where the difficulty met when attending online seminars using webinar media. In general, webinar applications lack sign language interpreting features, confusing webinar participants with hearing loss in understanding what the speaker is talking about. This webinar platform can display sign language translators according to the sentences spoken by the speaker. These study results are expected to help create a webinar platform with features that make it easier for participants with hearing disabilities to understand the material quickly.